1997
DOI: 10.1889/1.1985172
|View full text |Cite
|
Sign up to set email alerts
|

Organic multicolor EL display with fine pixels

Abstract: Abstract— We present a RGB multicolor EL display, in which a blue organic EL display was combined with color‐changing media (CCM). The CCMs were basically made up of organic fluorescent media which changed the emission color from blue to green or red.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…We also have reported a high efficiency of 6 lm/W and a half-lifetime of 20,000 hour at an initial luminance of 100 nits under a constant current driving. 5 In this report, DSA as the host material and SA as the dopant are referred to as IDE120 and IDE102, respectively. Recently, we found that a new oligo-amine, IDE406, was useful for the hole-injection layer, due to the high hole mobility and high glass-transition temperature.…”
Section: Light-blue Elmentioning
confidence: 99%
See 1 more Smart Citation
“…We also have reported a high efficiency of 6 lm/W and a half-lifetime of 20,000 hour at an initial luminance of 100 nits under a constant current driving. 5 In this report, DSA as the host material and SA as the dopant are referred to as IDE120 and IDE102, respectively. Recently, we found that a new oligo-amine, IDE406, was useful for the hole-injection layer, due to the high hole mobility and high glass-transition temperature.…”
Section: Light-blue Elmentioning
confidence: 99%
“…On the way, we found a new hole-injection material, dopants, and electrode material to improve the device performance. [2][3][4][5][6][7][8][9] After the long and difficult research, our blue EL material was commercialized for the use in our first organic EL product with an area-color feature in 1999. Note that the pioneer group succeeded in fabricating monochromatic green displays as a commercial product in 1997.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we report on progress achieved in the development of color changing media (CCM) [1] for color OLED microdisplays. Color displays utilizing monochrome blue OLED pixels with fluorescent CCM on top of them were invented by researchers from Idemitsu Kosan and Eastman Kodak [2]. In principle, this approach allows better performance than white displays with color filters on top [3], because no light is lost through filter absorption.…”
Section: Introductionmentioning
confidence: 99%
“…There are several approaches to color OLED displays, among them: pixels emitting blue light with fluorescing color changing media (CCM) on top of them [1]; pixels emitting white light with color filters on top of them [2]; and self-emissive pixelated display with RGB pixels placed next to each other [3]. In principle, the latter approach allows the best possible performance because no light is lost for filter absorption or color conversion.…”
Section: Introductionmentioning
confidence: 99%
“…CCM and/or color filters can be patterned independently and then aligned on top of OLED pixels. The design that uses a monochrome pixelated display with CCM was introduced for OLED displays by the researchers from the Idemitsu Kosan and Eastman Kodak Companies [1] and is shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%